Feasibility of robot‑assisted radical cystectomy in a patient with an ectopic kidney: A case report. (2023) - Edamura, Kohei; Sadahira, Takuya; Hara, Junya; Iwata, Takehiro; Ando, Wataru; Horii, Satoshi
No abstract available